2023
DOI: 10.3389/fimmu.2023.1162799
|View full text |Cite
|
Sign up to set email alerts
|

Loss of interleukin-1 beta is not protective in the lupus-prone NZM2328 mouse model

Abstract: Aberrant activation of the innate immune system is a known driver of lupus pathogenesis. Inhibition of the inflammasome and its downstream signaling components in murine models of lupus has been shown to reduce the severity of disease. Interleukin-1 beta (IL-1β) is a proinflammatory cytokine released from cells following inflammasome activation. Here, we examine how loss of IL-1β affects disease severity in the lupus-prone NZM2328 mouse model. We observed a sex-biased increase in immune complex deposition in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…As expected, individuals with SLE carry an inflammatory burden that is partly mediated by proinflammatory cytokines; the levels of the cytokines IL-6 and IL-18 are usually increased in these patients and are correlated with disease activity, 21 22 yet the serum IL-1β level in patients with SLE is still unclear. 23 We measured the cytokine levels in the serum and found that the levels of both cytokines were significantly greater in the SLE population (p<0.0001, figure 2A, C , online supplemental table S2 ). We also observed that the increased levels of both IL-6 and IL-1β were not significantly different between patients with active and remission SLE ( figure 2B, D ).…”
Section: Resultsmentioning
confidence: 95%
“…As expected, individuals with SLE carry an inflammatory burden that is partly mediated by proinflammatory cytokines; the levels of the cytokines IL-6 and IL-18 are usually increased in these patients and are correlated with disease activity, 21 22 yet the serum IL-1β level in patients with SLE is still unclear. 23 We measured the cytokine levels in the serum and found that the levels of both cytokines were significantly greater in the SLE population (p<0.0001, figure 2A, C , online supplemental table S2 ). We also observed that the increased levels of both IL-6 and IL-1β were not significantly different between patients with active and remission SLE ( figure 2B, D ).…”
Section: Resultsmentioning
confidence: 95%
“…Notably, experimental studies utilizing lupus models have provided compelling evidence supporting the link between increased expression of IL-1β and the severity and accelerated progression of the disease 66 , 67 . IL-1β knockout in lupus-prone NZM2328 mice still leads to the development of lupus phenotypes 68 . This finding suggested that the other signaling pathway is required for lupus development in NZM2328 mice.…”
Section: Discussionmentioning
confidence: 99%
“…Myd88 −/− MRL.Fas lpr mice have markedly reduced autoimmunity with ameliorated nephritis and dermatitis, loss of autoantibody production, and dampened immune activation ( Nickerson et al, 2010 ; Sadanaga et al, 2007 ). Furthermore, mice with deletion of both the TLR7 and TLR9 alleles recapitulated the majority of the Myd88 −/− MRL.Fas lpr phenotype, which suggests that MyD88 potentiation of disease resides downstream of these two endosomal TLRs ( Nickerson et al, 2010 ) and is independent of IL-1 signaling ( Loftus et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%